The Level of Social Intelligence of Secondary- ‎school Principals in the Irbid District and Its ‎Relationship to Their Job Performance - Al-Khaza’leh ‎, Khmaa’ael; Al-Omary, Haidar (Jordan Journal of Educational Sciences, 2021)
This study aimed to determine the level of social intelligence and job performance of secondary-school principals in the educational directorate of Irbid and to reveal the extent of the presence of statistically significant differences at the level of significance (α=0.05) in the averages of the sample members’ assessment of the level of social intelligence and job performance of secondary-school principals in the educational directorate of Irbid attributed to the variables of (gender, educational qualification and years of service). To achieve the goals of the study and answer its questions, a descriptive, correlational approach was used and the study sample was chosen by the simple random method to represent 7% of the study population during the academic year (2019/2020), where (200) questionnaires were distributed. The sample consisted of (189) male and female teachers. The results showed that the level of social intelligence among secondary-school principals in the educational directorate of Irbid from the teachers’ point of view was high and the level of job performance of secondary-school principals in the educational directorate of Irbid from the teachers’ point of view was high. In light of the study results, the study recommended maintaining and reinforcing this degree through holding an integrated program of different courses and training programs, aa well as specialized workshops in this aspect